Pengaruh Bukti Fisik, Suasana Ruangan, Dan Harga Terhadap Loyalitas Pelanggan Warunk Upnormal Bogor - Christian Andi Wijaya; Anton Widio Pratomo (Prodi Pariwisata dan LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
The purpose of this research is to find out how much influence of physical evidence, room atmosphere, and price on customer loyalty. Data type of research is quantitative explanation research instruments using questionnaires. Sampel for this research is 100 respondents who were Bogor resident visited and make purchase in Warunk Upnormal Bogor. Analitycal tool used regression analysis and testing hipotesis in this research using formula t count with result physical evidence (5,343>1,66), room atmosphere (-0,610<1,66), price (5,517>1,66) and f count with result (31,909>2,70) with SPSS program version 23 for macintosh. Based on the result of the research noted that physical evidence and price have positive effect and significant on customer loyalty while room atmosphere have no effect on customer loyalty and all three independent variable can determine changes in value from dependent variable as big as 49,9%. While partially, physical evidence variable have positive effect and significant on customer loyalty, room atmosphere variable have no effect on customer loyalty, and price variable have positive effect and significant on customer loyalty. This shows that there is a direct influence between independent variable and dependent variable simultaneously while partially, physical evidence and price have direct influence on customer loyalty while room atmosphere have no direct influence on customer loyalty. Keyword: Physical Evidence, Room Atmosphere, Price, Customer Loyalty